Cost-effectiveness of low-dose CT screening for lung cancer in a European country with high prevalence of smoking—A modelling study. (July 2018) - Tomonaga, Yuki; ten Haaf, Kevin; Frauenfelder, Thomas; Kohler, Malcolm; Kouyos, Roger D.; Shilaih, Mohaned; Lorez, Matthias; de Koning, Harry J.; Schwenkglenks, Matthias; Puhan, Milo A.
Highlights: Lung cancer screening may be cost-effective in European countries with high smoking prevalence. The most promising screening scenarios reduced lung cancer mortality by 6–15%. Systematic screening may increase the number of diagnosed lung cancers by 2–6%. The most cost-effective annual screening scenarios included heavy smokers aged 60–80 years. Abstract: Objectives: In Europe, there is uncertainty about the potential effects and cost-effectiveness of low dose computed tomography screening for lung cancer and about the applicability of results of North American studies. We aimed to estimate the effects and cost-effectiveness of lung cancer screening in a population-based setting in Switzerland where the smoking prevalence is high. Materials and methods: The MIcrosimulation Screening ANalysis-Lung (MISCAN) model was adapted using country specific input parameters regarding lung cancer epidemiology, smoking behaviours, and treatment costs. The effects and costs of 648 screening scenarios with different screening start and stop ages, smoking eligibility criteria, and screening intervals were examined from a public healthcare system perspective across a lifetime horizon in a cohort born between 1935 and 1965. Results: All screening scenarios showed an increase in the total number of detected lung cancer cases and a decrease in lung cancer mortality. On the efficiency frontier, 15 of 27 scenarios showed incremental cost-effectiveness ratios below € 50, 000 per life year gained. These scenarios reduced lung cancer mortality by 6–15% while increasing incidence of lung cancer diagnoses by 2–6%. Conclusion: These results suggest that lung cancer screening may be cost-effective in Switzerland, a high-income, European country with high smoking prevalence.